Neurodevelopmental, cognitive and motor function: Practice recommendations in pediatric intestinal failure and transplantation- position statement of the International Intestinal Rehabilitation and Transplant Association allied health committee - Stephanie So; Catherine Patterson; Taru Palsa; Jemma Mears; Bianca C. Bondi; Sydney Dempster; Christina Belza (Intestinal Failure)
Background: The objective of this position statement was to provide evidence-based and expert-informed recommendations for the assessment and treatment of neurodevelopment in children with intestinal failure and those undergoing intestinal transplant. Material and methods: A literature review was conducted to identify and review research articles from 2000 to 2023 that reported on neurodevelopmental, neurocognitive and motor outcomes in children (0–18 years) with intestinal failure or intestinal transplant. Key recommendations to address these outcomes were made based on scientific evidence and expert-informed opinion Results: The impact of intestinal failure and transplant on developmental outcomes was established, along with key risk factors related to the disease that may result in poorer outcomes. The involvement of rehabilitation specialists was recommended as part of the multidisciplinary intestinal care team to provide assessment and treatment across all developmental domains from infancy onwards. Care teams should provide close follow-up which may include screening during out-patient clinic follow up, along with timely community referrals to address developmental delays. Children undergoing intestinal or multi-visceral transplant require assessment and treatment both pre and post-transplant to maximize developmental outcomes. Conclusions: This position paper reviews available literature related to developmental outcomes in intestinal failure and transplant, delineating risk factors which may contribute to poorer outcomes. It lays the foundation for tangible steps to assist intestinal care teams in advocating for the services of rehabilitation team members to provide ongoing assessment and treatment to optimize clinical outcomes.